MEMBACA PERBEDAAN JENDER DALAM MODEL CAREER INDESICION SISWA SEKOLAH MENENGAH ATAS - Muhammad Ali (Dialogia: Islamic Studies and Social Journal, 2016)
Abstract: This aim is to find career indecision model based on gender differences. Theoretically, model shows variables of gender roles, family support, career decision making self-efficacy, and willingness affect on career indecision results in both gender groups. Questionnaire was used to collect the data and the samples were 120 male and 260 female. Then the data was analyzed by SEM (Structural Equation Modeling). Then those indicated that there is distinguishes models on career indecision either male or female. Gender roles and family supports are not dominant factor that affect career indecision for male. While for female, career indecision is affected by gender roles and family supports. In addition, family supports affect the females’ willingness directly and in contrary with male. Then, this study suggests taking to heart on students’ cultural conditions when consulting students’ career.